Cross-cultural study the macro variables and its impact on exchange rate regimes - Muhammad Naveed Jamil; Abdul Rasheed; Adnan Maqbool; Zeeshan Mukhtar (Future Business Journal)
Abstract This is an empirical analysis of study simultaneously focus on examining the impact of macroeconomic variables, i.e., GDP growth, GDP per capita, inflation, foreign direct investment, exports, imports, interest rates, foreign debt and foreign reserves on the exchange rate regimes, using the sample of five countries from MSCI developed markets index, emerging markets index and frontier markets index each from 1970 to 2020. This study predicts and provides several essential contributions for markets, financial and economic, that fills the gaps in the markets economic and financial literacy of desired countries. The study identifies and evaluates the impact using the most advanced statistical frameworks. This study adopts ML—binary logit (quadratic hill climbing) and investigates the change in the exchange rate regimes due to macroeconomic variables. The empirical results confirm that Australia, Hong Kong, Japan, New Zealand and Singapore markets take timely correct exchange rate regimes decisions, which lead to developed markets. As emerging markets and frontier markets never adopt the exchange rate regimes three, four, and six, which is a significant impact factor that affects those markets never growth according develops markets. Foreign debts, inflation and foreign reserves are severe challenges for emerging and frontier markets.